Does the Business Environment Affect Corporate Investment in India? - Tokuoka, Kiichi (IMF Working Papers; Working Paper ;, 2012)
Since the global financial crisis, corporate investment has been weak in India. Sluggish corporate investment would not only moderate growth from the demand side but also constrain growth from the supply side over time. Against this background, this paper analyzes the reasons for the slowdown and discusses how India can boost corporate investment, using both macro and firm-level micro data. Analysis of macro data indicates that macroeconomic factors can largely explain corporate investment but that they do not appear to account fully for recent weak performance, suggesting a key role of the business environment in reviving corporate investment. Analysis of micro panel data suggests that improving the business environment by reducing costs of doing business, improving financial access, and developing infrastructure, could stimulate corporate investment.